PENGARUH PERLAKUAN AWAL SAMPAH ORGANIK TERHADAP PRODUKSI BIOGAS SECARA ANAEROBIC DIGESTION - Dhaniswara, Trisna Kumala; Fitri, Medya Ayunda (Journal of Research and Technology, 2017)
The biggest problem currently in Indonesia is accumulated and uncontrolled of garbage amount everywhere, especially organic waste. There are also more methods to utilize waste. One of waste utilization is Biogas. Organic content in organic waste can be used as a substart source for anaerobic bacteria. Initial treatment of organic waste in this study used as a variable, namely chopped and blended. This initial treatment was done before it was mixed with other materials, ie cattle dung and water. 200% water was added to the reactor along with other variables. Temperature, pH and biogas volume were observed for 30 days. Initial treatment factor of organic waste as biogas production substrat showed blend treatment with decay, it had higher biogas production than others. Biogas volume was resulted 189.99 cm3 with a composition ratio of 50% cattle dung and 50% organic waste.Keywords: Biogas, Livestock Manure, Organic Waste.